Analysis of Blockchain consensus mechanisms : Proof-of-Work vs Proof-of-Stake - Saif, Saba (My University, 2022)
The objective of this thesis is to understand and evaluate the two popular consensus mechanisms of blockchain: Proof-of-Work (PoW) and Proof-of-Stake (PoS), especially in terms of their cost effectiveness. This study attempts to answer one significant research question: “Researchers assume that blockchain cannot takeover computer networks, as it requires excessive computation power. If blockchain moved to a Proof-of-Stake (PoS) consensus algorithm would takeovers remain equally difficult?” The thesis uses qualitative desk research approach by utilizing the existing research papers and published reports related to the topic. It attempts to draw comparison between both consensus algorithms and extracts reasonable conclusions based on the simulation experiment results. The three main comparison points discussed among the consensus protocols are energy consumption, decentralization, and security of blockchain. This study concludes that Proof-of-Stake (PoS) consumes less energy than the Proof-of-Work (PoW) and also shows better results in providing decentralization and security as compared to Proof-of-Work (PoW). Hence, takeovers are easier with PoS over PoW, but PoS still has room for improvement to reduce the required energy resources and further research studies are needed to analyse it.
Keywords: Blockchain, Consensus Mechanism, Proof-of-Work, Proof-of-Stake, Energy Consumption, Cost Efficiency